Analysis and Design of Outphasing Transmitter Using Class-E Power Amplifiers With Shunt Capacitances and Shunt Filters - Pavel Afanasyev (IEEE Access, 2020)
In this paper, a novel outphasing power amplifier (PA) based on class-E amplifiers with shunt capacitances and shunt filters is proposed. The new design provides high drain efficiency for both peak and back-off power levels. A mathematical model for the class-E power amplifier with shunt capacitance and shunt filter is presented. The proposed model enables derivation of load circuit parameters that provide optimum drain efficiency for the peak and back-off power levels using closed form mathematical expressions. Based on this model, an outphasing power amplifier is designed and subsequently implemented using microstrip transmission lines and a GaN HEMT devices. The fabricated power amplifier prototype is optimized for 2.14 GHz and provides drain efficiency of over 60% for back-off power levels up to 8.5 dB. The amplifier demonstrates a 44.3% drain efficiency for 64QAM OFDM modulated signal with 20 MHz bandwidth. Adjacent channel leakage ratio (ACLR) of -39.5 dB and error vector magnitude (EVM) of 0.9 % were achieved after the application of a memory polynomial linearization algorithm.